Discourse Analysis of Emoji Use in Digital Communication by the Millennials & Gen Z: A Comparative Endeavor (The Journal of Cultural Perspectives, 2025)
This research examines the generational differences in emoji usage and the meanings attributed to them between the Millennials and Gen Z, using Speech Act Theory as developed by Austin and Searle in 1979. Traditionally seen as pictorial aids for emotion, emojis have evolved into semiotic tools that perform complex communicative functions. This research aims to probe how emojis function figuratively as speech acts and in what way their meanings differ across generations. The objectives include identifying patterns in emoji interpretation and usage among Millennials and Gen Z, and examining the role of cultural knowledge in shaping these meanings. This research employs Speech Act Theory as its primary methodological framework to analyze how each generation assigns meaning to emojis in digital conversations. The findings reveal that the Millennials often use emojis to clarify, soften, or support the tone of their messages, thus reflecting more straightforward locutionary and illocutionary acts. They use emojis according to their conventional or dictionary meanings. Gen Z, on the other hand, tends to employ them to convey much more complex and often ironic meanings. Such layered meanings are thus created with their shared cultural knowledge and in-group references. The research findings also suggest that emojis have an important performative role in digital communication. The significance of this study lies in highlighting how emojis serve not only emotional expression but also help to understand communication gaps across age groups and identity formation and generational belonging. They are useful resources for representing emotions and generational belonging, beyond simple decorative pictorial representations, and describes how differences in emoji interpretation can create miscommunication between generations. Overall, this research illustrates the dynamic and negotiated ways meaning merges in digital discourse by the use of emojis across two different generations.